NOISE REDUCTION OF WOODWORKING MACHINES BY REVERBERATION CHAMBER - Satylgan, K.N.; Shaltabaeva, S.T.; Kurmanbekova, E.B. (Journal of Emerging Technologies and Computing, 2020)
The issues of noise reduction in woodworking industries aregetting worse every year. Noise suppression has become a relevant problem ofour time, since its solution can, on the one hand, guarantee normal workingconditions, free up auxiliary resources to increase labor productivity, whichultimately fully justifies the material labor costs for noise control. Now it is moreadvantageous for the business owner not to invest reserves in the engineeringand technical renewal of their enterprises, but to use outdated woodworkingequipment, regularly carrying out regular repairs. Improving working conditionsat small woodworking enterprises according to the noise criterion - the mainharmful production criterion-is relevant. The publication provides a sample ofnoise reduction on woodworking machines using a reverberation chamber.